2008
DOI: 10.1080/15563650701639097
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent life-threatening ventricular dysrhythmias associated with acute hydrofluoric acid ingestion: Observations in one case and implications for mechanism of toxicity

Abstract: University of Texas, Southwestern Medical Center at Dallas, Dallas, Texas, USAIntroduction. Hydrofluoric acid (HF) is a weak inorganic acid used for etching and as rust remover. Systemic toxicity is manifested as ventricular dysrhythmias. The mechanisms for these dysrhythmias are not well elucidated. Case report. An 82-year-old woman ingested 8 ounces of 7% HF. Shortly after emergency department (ED) arrival, she became pulseless, developing recurrent ventricular dysrhythmias. She was defibrillated 17 times an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 36 publications
2
29
0
3
Order By: Relevance
“…Gardos showed that this potassium efflux had an absolute calcium requirement, and that raising serum calcium when treating fluoridepoisoned patients leads to increased extracellular potassium from erythrocytes [21,28]. This is tempered by several human case reports noting normal potassium levels, hypocalcemia, and fatal dysrhythmias in fluoride-poisoned patients [12]. It is always difficult to discern causality within these case reports without frequent serial measurements of electrolytes relative to observed dysrhythmias.…”
Section: Case Continuationmentioning
confidence: 88%
See 2 more Smart Citations
“…Gardos showed that this potassium efflux had an absolute calcium requirement, and that raising serum calcium when treating fluoridepoisoned patients leads to increased extracellular potassium from erythrocytes [21,28]. This is tempered by several human case reports noting normal potassium levels, hypocalcemia, and fatal dysrhythmias in fluoride-poisoned patients [12]. It is always difficult to discern causality within these case reports without frequent serial measurements of electrolytes relative to observed dysrhythmias.…”
Section: Case Continuationmentioning
confidence: 88%
“…All of these compounds are potentially lethal. Sodium fluoride is highly soluble and readily liberates fluoride ion, while hydrofluoric acid is a weak acid that does not easily disassociate [12]. Ammonium bifluoride readily dissociates after ingestion to hydrofluoric acid and free fluoride ion [6].…”
Section: How Does Hydrofluoric Acid Differ From Other Caustics?mentioning
confidence: 99%
See 1 more Smart Citation
“…Hsps are among the major defensive stress proteins, which play an important role in the pathophysiology of various xenobiotic-induced cardiotoxicity models (Shan et al 2003;Yu et al 2012). Acute F − poisoning is known to cause sudden cardiac failure in both humans (Vohra et al 2008;Lech 2011) and experimental animals (McIvor et al 1987). Our previous study showed that acute F − exposure impairs cardiac dysfunction through increased mitochondrial oxidative damage, apoptosis, and necrosis in rat myocardium .…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was well studied that electrolyte imbalances, increased intracellular calcium-, hypocalcemia-, and hyperkalemia-mediated ventricular arrhythmias were the decisive events in the cardiac pathophysiology of acute F − poisoning in both human case studies (Kumar 2009;Takase et al 2004;Vohra et al 2008) and experimental models . In addition, F − alters the mitochondrial membrane potential in H9c2 cells and inhibits oxidative phosphorylation in rat cardiac mitochondria (Pacauskiene et al 2009;Yan et al 2015).…”
Section: Introductionmentioning
confidence: 99%